Smoking and drinking habits before and during pregnancy in Spanish women. Issue 1 (February 1994) - Bolumar, F; Rebagliato, M; Hernandez-Aguado, I; Florey, C D
Abstract : STUDY OBJECTIVE--To investigate possible changes in smoking and drinking habits during pregnancy and to elucidate the sociodemographic factors associated with these changes in Spanish women. DESIGN--A cross-sectional survey. PARTICIPANTS AND SETTING--A total of 1004 pregnant women of between 12 and 18 weeks of gestation who were attending the antenatal clinic of the main regional hospital of Valencia (Spain) during 1989 were studied. All participants completed the study and only one eligible woman refused to participate when approached. MEASUREMENTS AND MAIN RESULTS--Information was obtained by structured questionnaire (Euromac questionnaire), which included items on age, educational level, marital status, occupation, parity, previous and present smoking habits, and previous and present alcohol consumption. Women were asked about the consumption of cigarettes and alcohol for a typical week before they knew they were pregnant, and details of current consumption were obtained for the week before the interview. The number of drinks taken per week was later converted to the amount of absolute alcohol (in g). Sixty per cent of the women smoked and 72% drank alcohol before pregnancy. Forty eight per cent of smokers stopped smoking and 37% of drinkers stopped drinking alcohol during pregnancy. No sociodemographic factor showed an independent association with either smoking or drinking cessation. Only the number of cigarettes and the amount of alcohol consumed before pregnancy were identified as significant independent predictors for stopping. CONCLUSIONS--Pregnant Spanish women seemed to stop smoking at about three times the rate found in Spanish women in the reproductive years. The sociodemographic variables usually associated with stopping smoking could not account for the high rate of quitting in these Spanish women, a rate higher than that in women from other developed countries. The high prevalence of smoking before pregnancy might explain not only the high rate of stopping smoking but also the absence of a well defined profile of "quitters". In our study, high levels of alcohol consumption were limited to a small group of pregnant women, and preventive efforts should be focused on this group.